Light‐Activated Decellularized Extracellular Matrix‐Based Bioinks for Volumetric Tissue Analogs at the Centimeter Scale. (13th May 2021) - Kim, Hyeonji; Kang, Byeongmin; Cui, Xiaolin; Lee, Se‐Hwan; Lee, Kwangseok; Cho, Dong‐Woo; Hwang, Woonbong; Woodfield, Tim B. F.; Lim, Khoon S.; Jang, Jinah
Abstract: Tissue engineering requires not only tissue‐specific functionality but also a realistic scale. Decellularized extracellular matrix (dECM) is presently applied to the extrusion‐based 3D printing technology. It has demonstrated excellent efficiency as bioscaffolds that allow engineering of living constructs with elaborate microarchitectures as well as the tissue‐specific biochemical milieu of target tissues and organs. However, dECM bioinks have poor printability and physical properties, resulting in limited shape fidelity and scalability. In this study, new light‐activated dECM bioinks with ruthenium/sodium persulfate (dERS) are introduced. The materials can be polymerized via a dityrosine‐based cross‐linking system with rapid reaction kinetics and improved mechanical properties. Complicated constructs with high aspect ratios can be fabricated similar to the geometry of the desired constructs with increased shape fidelity and excellent printing versatility using dERS. Furthermore, living tissue constructs can be safely fabricated with excellent tissue regenerative capacity identical to that of pure dECM. dERS may serve as a platform for a wider biofabrication window through building complex and centimeter‐scale living constructs as well as supporting tissue‐specific performances to encapsulated cells. This capability of dERS opens new avenues for upscaling the production of hydrogel‐based constructs without additional materials and processes, applicable in tissue engineering and regenerative medicine. Abstract : New light‐activated decellularized extracellular bioinks with ruthenium/sodium persulfate (dERS) are cured through a rapid dityrosine‐based cross‐linking reaction. dERS enables the bioprinting of complex structures with increased shape fidelity and highly improved printing versatility. The cell‐laden constructs also exhibit excellent tissue regenerative capacity. These capabilities of dERS open new avenues for the production of clinically relevant soft tissues applicable in tissue engineering field.